Fibrous carbon nanostructure, evaluation method of fibrous carbon nanostructure and production method of surface-modified fibrous carbon nanostructure
Patent Information
- Application Number
- JP2024195441
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2017-12-19
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2038-11-30
AI Technical Summary
【0017】 本発明によれば、表面改質処理し易い繊維状炭素ナノ構造体を提供することができる。 また、本発明によれば、良好に表面改質処理された表面改質繊維状炭素ナノ構造体を提供することができる。
Smart Images

Figure 2025020340000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a fibrous carbon nanostructure, a method for evaluating a fibrous carbon nanostructure, and a method for producing a surface-modified fibrous carbon nanostructure. [Background technology]
[0002] In recent years, fibrous carbon nanostructures such as carbon nanotubes (hereinafter sometimes referred to as "CNTs") have been attracting attention as materials with excellent electrical conductivity, thermal conductivity and mechanical properties.
[0003] However, fibrous carbon nanostructures such as CNTs tend to form bundle structures due to van der Waals forces and are difficult to disperse in solvents or resins, making it difficult to achieve the desired high properties.
[0004] In view of this, a technique has been proposed for improving the dispersibility of fibrous carbon nanostructures such as CNTs by subjecting the fibrous carbon nanostructures to a surface modification treatment such as an oxidation treatment (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2015 / 045418 Summary of the Invention [Problem to be solved by the invention]
[0006] Here, from the viewpoint of obtaining surface-modified fibrous carbon nanostructures with excellent dispersibility by surface modification treatment of the fibrous carbon nanostructures, it is necessary to perform a good surface modification treatment on the raw material fibrous carbon nanostructures.
[0007] However, conventional fibrous carbon nanostructures have room for improvement in terms of the ease with which they can be subjected to surface modification treatment.
[0008] Therefore, an object of the present invention is to provide a fibrous carbon nanostructure that is easy to subject to surface modification treatment. Another object of the present invention is to provide a surface-modified fibrous carbon nanostructure which has been subjected to a satisfactory surface modification treatment. [Means for solving the problem]
[0009] The present inventors have conducted extensive research in order to achieve the above object, and have found that fibrous carbon nanostructures having predetermined properties are easily surface-modified, thereby completing the present invention.
[0010] That is, the present invention has an object to advantageously solve the above-mentioned problems, and the fibrous carbon nanostructure of the present invention is characterized in that the symmetry coefficient of the peak of the first differential curve of the thermogravimetric curve obtained by thermogravimetric analysis in a dry air atmosphere is 3.70 or less. Fibrous carbon nanostructures having a symmetry coefficient of the peak of the first differential curve of the thermogravimetric curve of 3.70 or less are easily surface-modified when subjected to a surface modification treatment such as an oxidation treatment. In the present invention, the "peak symmetry coefficient" can be determined by the method described in the Examples of this specification.
[0011] Here, the first derivative curve may be a temperature derivative curve or a time derivative curve of the thermogravimetric curve.
[0012] In addition, the fibrous carbon nanostructure of the present invention preferably exhibits an upwardly convex t-plot obtained from the adsorption isotherm, because the fibrous carbon nanostructure exhibiting an upwardly convex t-plot can exhibit particularly excellent properties (e.g., electrical conductivity, thermal conductivity, strength, etc.) when the dispersibility is enhanced by a surface modification treatment.
[0013] Furthermore, the fibrous carbon nanostructure of the present invention preferably has a bending point of the t-plot in the range of 0.2≦t(nm)≦1.5, because the fibrous carbon nanostructure having a bending point of the t-plot in the above range can exhibit particularly excellent properties (e.g., electrical conductivity, thermal conductivity, strength, etc.) when the dispersibility is enhanced by a surface modification treatment.
[0014] In addition, it is preferable that the total specific surface area S1 and the internal specific surface area S2 obtained from a t-plot obtained from the adsorption isotherm of the fibrous carbon nanostructure of the present invention satisfy the relation: 0.05≦S2 / S1≦0.30. This is because the fibrous carbon nanostructure having S2 / S1 within the above range can exhibit particularly excellent properties (e.g., electrical conductivity, thermal conductivity, strength, etc.) when the dispersibility is enhanced by a surface modification treatment.
[0015] The fibrous carbon nanostructure of the present invention preferably contains carbon nanotubes, and more preferably contains single-walled carbon nanotubes, because the fibrous carbon nanostructure containing carbon nanotubes, particularly the fibrous carbon nanostructure containing single-walled carbon nanotubes, can exhibit particularly excellent properties (e.g., electrical conductivity, thermal conductivity, strength, etc.) when the dispersibility is enhanced by a surface modification treatment.
[0016] In addition, the present invention aims to advantageously solve the above-mentioned problems, and is characterized in that the method for evaluating fibrous carbon nanostructures of the present invention includes the steps of performing thermogravimetric analysis of fibrous carbon nanostructures under a dry air atmosphere to obtain a first differential curve of the thermogravimetric curve, determining the symmetry coefficient of the peak of the first differential curve of the thermogravimetric curve, and judging those whose symmetry coefficient is 3.70 or less to be good products and those whose symmetry coefficient is greater than 3.70 to be defective products. The manufacturing method for surface-modified fibrous carbon nanostructures of the present invention is characterized by including a step of evaluating fibrous carbon nanostructures using the above-mentioned method for evaluating fibrous carbon nanostructures, and a step of subjecting fibrous carbon nanostructures judged to be good products to a surface modification treatment to obtain surface-modified fibrous carbon nanostructures. Effect of the Invention
[0017] According to the present invention, it is possible to provide a fibrous carbon nanostructure which is easy to subject to a surface modification treatment. Furthermore, according to the present invention, it is possible to provide a surface-modified fibrous carbon nanostructure which has been subjected to a satisfactory surface modification treatment. [Brief description of the drawings]
[0018] [Figure 1] 1A and 1B are graphs showing schematic shapes of peaks of first derivative curves of thermogravimetry curves, where FIG. 1A shows a case where the first derivative curve is a temperature derivative curve, and FIG. 1B shows a case where the first derivative curve is a time derivative curve. [Diagram 2] 1 is a graph showing first derivative curves of thermogravimetric curves of fibrous carbon nanostructures of Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, an embodiment of the present invention will be described in detail. Here, the fibrous carbon nanostructure of the present invention is easily surface-modified when subjected to a surface modification treatment such as an oxidation treatment, etc. The surface-modified fibrous carbon nanostructure obtained by subjecting the fibrous carbon nanostructure of the present invention to a surface modification treatment is not particularly limited, and can be suitably used, for example, when preparing a dispersion liquid in which the surface-modified fibrous carbon nanostructure is dispersed in a dispersion medium.
[0020] (fibrous carbon nanostructures) The fibrous carbon nanostructure of the present invention is required to have a symmetry coefficient of 3.70 or less at the peak of the first differential curve of the thermogravimetric curve obtained by thermogravimetric analysis in a dry air atmosphere. Since the symmetry coefficient of the peak of the first differential curve of the thermogravimetric curve of the fibrous carbon nanostructure of the present invention is 3.70 or less, the surface of the fibrous carbon nanostructure is favorably modified when subjected to a surface modification treatment such as an oxidation treatment.
[0021] Here, the fibrous carbon nanostructure is not particularly limited, and examples thereof include cylindrical carbon nanostructures such as carbon nanotubes (CNTs) and non-cylindrical carbon nanostructures such as carbon nanostructures in which a six-membered carbon ring network is formed into a flattened cylinder. The fibrous carbon nanostructure of the present invention may contain one kind of the above-mentioned carbon nanostructure alone, or may contain two or more kinds of them.
[0022] Among the above, the fibrous carbon nanostructure is preferably a fibrous carbon nanostructure containing CNT, because the fibrous carbon nanostructure containing CNT can exhibit particularly excellent properties (e.g., electrical conductivity, thermal conductivity, strength, etc.) when the dispersibility is increased by a surface modification treatment.
[0023] The fibrous carbon nanostructure containing CNT may be composed only of CNT, or may be a mixture of CNT and a fibrous carbon nanostructure other than CNT. The CNT in the fibrous carbon nanostructure is not particularly limited, and single-walled carbon nanotubes and / or multi-walled carbon nanotubes can be used, but the CNT is preferably a single-walled to five-walled carbon nanotube, and more preferably a single-walled carbon nanotube, because the fewer the number of walls of the carbon nanotube, the more excellent the properties can be exhibited when the dispersibility is increased by surface modification treatment.
[0024] Here, the fibrous carbon nanostructure of the present invention must have a symmetry coefficient of 3.70 or less at the peak of the first differential curve of the thermogravimetric curve obtained by thermogravimetric analysis under a dry air atmosphere, and the symmetry coefficient of the peak of the first differential curve of the thermogravimetric curve is preferably 3.30 or less, more preferably 2.60 or less, and even more preferably 2.00 or less. The symmetry coefficient of the peak of the first differential curve of the thermogravimetric curve of the fibrous carbon nanostructure is preferably 0.50 or more, more preferably 0.70 or more, and even more preferably 0.80 or more. If the symmetry coefficient of the peak of the first differential curve is within the above range, the surface is more easily modified when a surface modification treatment such as an oxidation treatment is performed.
[0025] The thermogravimetric curve may be a thermogravimetric curve with the vertical axis representing mass and the horizontal axis representing temperature, or may be a thermogravimetric curve with the vertical axis representing mass and the horizontal axis representing time. The first derivative curve of the thermogravimetric curve may be a temperature derivative curve with the vertical axis representing differential thermogravimetry (DTG) and the horizontal axis representing temperature, or may be a time derivative curve with the vertical axis representing differential thermogravimetry (DTG) and the horizontal axis representing time. Here, when the first differential curve is a temperature differential curve, the peak top of the first differential curve is usually located within a range of 500 to 800° C. When the first differential curve is a time differential curve, the peak top of the first differential curve is usually located within a range of 20×v to 36×v minutes (for example, within a range of 100 to 180 minutes when the heating rate is 5° C. / min), where v is the heating rate during thermogravimetric analysis.
[0026] Furthermore, the magnitude of the symmetry coefficient of the peak of the first differential curve of the thermogravimetric curve of the fibrous carbon nanostructure is not particularly limited, and can be adjusted by changing the synthesis conditions of the fibrous carbon nanostructure (e.g., the composition of the raw material gas, the type of catalyst used in the synthesis, etc.).
[0027] The average diameter of the fibrous carbon nanostructure is preferably 1 nm or more, more preferably 60 nm or less, more preferably 30 nm or less, and even more preferably 10 nm or less. The fibrous carbon nanostructure having an average diameter within the above range can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment. Here, in the present invention, the "average diameter of fibrous carbon nanostructures" can be determined by measuring the diameter (outer diameter) of, for example, 20 fibrous carbon nanostructures on a transmission electron microscope (TEM) image and calculating the number average value.
[0028] In addition, as the fibrous carbon nanostructure, it is preferable to use a fibrous carbon nanostructure having a ratio (3σ / Av) of the value (3σ) obtained by multiplying the standard deviation of the diameter (σ: sample standard deviation) by 3 to the average diameter (Av) of more than 0.20 and less than 0.60, more preferably a fibrous carbon nanostructure having a 3σ / Av of more than 0.25, and even more preferably a fibrous carbon nanostructure having a 3σ / Av of more than 0.50. Fibrous carbon nanostructures having a 3σ / Av of more than 0.20 and less than 0.60 can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment. The average diameter (Av) and standard deviation (σ) of the fibrous carbon nanostructures may be adjusted by changing the manufacturing method or manufacturing conditions of the fibrous carbon nanostructures, or by combining multiple types of fibrous carbon nanostructures obtained by different manufacturing methods.
[0029] Furthermore, the average length of the fibrous carbon nanostructure is preferably 10 μm or more, more preferably 50 μm or more, and even more preferably 80 μm or more, and is preferably 600 μm or less, more preferably 550 μm or less, and even more preferably 500 μm or less. The fibrous carbon nanostructure having an average length within the above range can exhibit particularly excellent properties when its dispersibility is enhanced by a surface modification treatment. In the present invention, the "average length of fibrous carbon nanostructures" can be determined by measuring the lengths of, for example, 20 fibrous carbon nanostructures on a scanning electron microscope (SEM) image and calculating the number-average value.
[0030] Here, the fibrous carbon nanostructure usually has an aspect ratio of more than 10. The aspect ratio of the fibrous carbon nanostructure can be determined by measuring the diameter and length of 20 randomly selected fibrous carbon nanostructures using a scanning electron microscope or a transmission electron microscope and calculating the average value of the ratio of the diameter to the length (length / diameter).
[0031] In addition, the fibrous carbon nanostructure has a BET specific surface area of 600 m 2 / g or more, and 2 / g or more is more preferable, and 2000m 2 / g or less, and 2 / g or less is more preferable, and 1600m 2 It is more preferable that the BET specific surface area of the fibrous carbon nanostructure is 600 m 2 When the BET specific surface area of the fibrous carbon nanostructure is 2000 m / g or more, it can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment. 2 If the molecular weight is 1.0 to 1.0 g, the dispersibility can be sufficiently increased when the surface is modified.
[0032] In addition, the fibrous carbon nanostructure preferably has a t-plot obtained from the adsorption isotherm that shows an upwardly convex shape. The fibrous carbon nanostructure having a t-plot that shows an upwardly convex shape can exhibit particularly excellent properties when the dispersibility is enhanced by a surface modification treatment. The "t-plot" can be obtained by converting the relative pressure into the average thickness t (nm) of the nitrogen gas adsorption layer in the adsorption isotherm of the fibrous carbon nanostructure measured by the nitrogen gas adsorption method. That is, the t-plot of the fibrous carbon nanostructure can be obtained by determining the average thickness t of the nitrogen gas adsorption layer corresponding to the relative pressure from a known standard isotherm in which the average thickness t of the nitrogen gas adsorption layer is plotted against the relative pressure P / P0, and performing the above conversion (t-plot method by de Boer et al.).
[0033] Here, in a material having pores on the surface, the growth of a nitrogen gas adsorption layer is classified into the following processes (1) to (3). The slope of the t-plot changes depending on the processes (1) to (3) below. (1) The process of forming a monolayer of nitrogen molecules on the entire surface (2) Formation of multilayer adsorption and the associated capillary condensation filling process in the pores (3) The formation of multilayer adsorption on an apparently non-porous surface whose pores are filled with nitrogen
[0034] In the t-plot showing an upward convex shape, the plot is located on a straight line passing through the origin in the region where the average thickness t of the nitrogen gas adsorption layer is small, whereas as t increases, the plot shifts downward from the straight line. Fibrous carbon nanostructures having such a t-plot shape have a large ratio of the internal specific surface area to the total specific surface area of the fibrous carbon nanostructure, indicating that a large number of openings are formed in the carbon nanostructures that make up the fibrous carbon nanostructure.
[0035] The inflection point of the t-plot of the fibrous carbon nanostructure is preferably in the range of 0.2≦t(nm)≦1.5, more preferably in the range of 0.45≦t(nm)≦1.5, and even more preferably in the range of 0.55≦t(nm)≦1.0. If the inflection point of the t-plot of the fibrous carbon nanostructure is in this range, it can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment. The "position of the bending point" is the intersection of the approximation line A in the above-mentioned process (1) and the approximation line B in the above-mentioned process (3).
[0036] Furthermore, the fibrous carbon nanostructure preferably has a ratio (S2 / S1) of the internal specific surface area S2 to the total specific surface area S1 obtained from a t-plot of 0.05 to 0.30. If the S2 / S1 value of the fibrous carbon nanostructure is within this range, it can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment. Here, the total specific surface area S1 and the internal specific surface area S2 of the fibrous carbon nanostructure can be obtained from the t-plot. Specifically, first, the total specific surface area S1 can be obtained from the slope of the approximation line in step (1), and the external specific surface area S3 can be obtained from the slope of the approximation line in step (3). Then, the internal specific surface area S2 can be calculated by subtracting the external specific surface area S3 from the total specific surface area S1.
[0037] Incidentally, the measurement of the adsorption isotherm of the fibrous carbon nanostructure, the creation of t-plots, and the calculation of the total specific surface area S1 and the internal specific surface area S2 based on the analysis of the t-plots can be performed, for example, using a commercially available measuring device, "BELSORP (registered trademark)-mini" (manufactured by BEL Japan Co., Ltd.).
[0038] Furthermore, the fibrous carbon nanostructure containing CNTs suitable for the fibrous carbon nanostructure preferably has a radial breathing mode (RBM) peak when evaluated by Raman spectroscopy. Note that the Raman spectrum of a fibrous carbon nanostructure consisting only of multi-walled carbon nanotubes having three or more walls does not have an RBM.
[0039] In addition, the fibrous carbon nanostructure containing CNTs preferably has a ratio of G band peak intensity to D band peak intensity in a Raman spectrum (G / D ratio) of 0.5 to 5.0. If the G / D ratio is 0.5 to 5.0, the nanostructure can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment.
[0040] The carbon purity of the fibrous carbon nanostructure is preferably 98% by mass or more, more preferably 99% by mass or more, and further preferably 99.9% by mass or more.
[0041] (Method of manufacturing fibrous carbon nanostructures) In addition, fibrous carbon nanostructures having the above-mentioned properties can be efficiently produced, for example, by a method in which raw material compounds and a carrier gas are supplied to a substrate having a catalyst layer on its surface to synthesize a fibrous carbon nanostructure by a CVD method, and the catalytic activity of the catalyst layer is dramatically improved by having a trace amount of oxidant (catalyst activation material) present in the system (see, for example, International Publication No. 2006 / 011655), in which the catalyst layer is formed on the substrate surface by a wet process and a raw material gas containing ethylene (for example, a gas containing more than 10 volume % ethylene).
[0042] Here, the formation of a catalyst layer on the surface of a substrate by a wet process can be carried out, for example, by applying coating liquid A containing an aluminum compound onto the substrate, drying coating liquid A to form an aluminum thin film (a catalyst-supported layer supporting an iron thin film (catalyst layer)) on the substrate, and then applying coating liquid B containing an iron compound onto the aluminum thin film, followed by drying coating liquid B to form an iron thin film (catalyst layer) on the aluminum thin film. Note that "aluminum thin film" refers to a thin film containing aluminum as a metal component, and "iron thin film" refers to a thin film containing iron as a metal component.
[0043] As the substrate, substrates made of metals such as iron, nickel, chromium, molybdenum, tungsten, titanium, aluminum, manganese, cobalt, copper, silver, gold, platinum, niobium, tantalum, lead, zinc, gallium, indium, germanium, and antimony, substrates made of alloys or oxides of these metals, substrates made of non-metals such as silicon, quartz, glass, mica, graphite, and diamond, or substrates made of ceramics can be used.
[0044] Furthermore, as the coating liquid A, a solution or dispersion in an organic solvent of a metal organic compound or a metal salt capable of forming an alumina thin film as the aluminum thin film can be used. Here, examples of metal organic compounds capable of forming an alumina thin film include aluminum alkoxides such as aluminum trimethoxide, aluminum triethoxide, aluminum tri-n-propoxide, aluminum tri-i-propoxide, aluminum tri-n-butoxide, aluminum tri-sec-butoxide, and aluminum tri-tert-butoxide. Other examples of metal organic compounds containing aluminum include complexes such as tris(acetylacetonato)aluminum(III). Examples of metal salts capable of forming an alumina thin film include aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum bromide, aluminum iodide, aluminum lactate, basic aluminum chloride, and basic aluminum nitrate. Furthermore, examples of organic solvents that can be used include various organic solvents such as alcohols, glycols, ketones, ethers, esters, and hydrocarbons. These can be used alone or as a mixture. A stabilizer for suppressing the condensation polymerization reaction of the metal organic compound and the metal salt may be added to the coating liquid A. The stabilizer is preferably at least one selected from the group consisting of β-diketones and alkanolamines. β-diketones include acetylacetone, methyl acetoacetate, ethyl acetoacetate, benzoylacetone, dibenzoylmethane, benzoyltrifluoroacetone, furoylacetone, and trifluoroacetylacetone, and it is particularly preferable to use acetylacetone and ethyl acetoacetate. Alkanolamines include monoethanolamine, diethanolamine, triethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, N,N-dimethylaminoethanol, diisopropanolamine, and triisopropanolamine, and it is preferable to use secondary or tertiary alkanolamine.
[0045] Furthermore, as the coating liquid B, a solution or dispersion of a metal organic compound or metal salt capable of forming an iron thin film in an organic solvent can be used. Here, examples of metal organic compounds capable of forming an iron thin film include iron pentacarbonyl, ferrocene, iron acetylacetonate (II), iron acetylacetonate (III), iron trifluoroacetylacetonate (II), iron trifluoroacetylacetonate (III), etc. Examples of metal salts capable of forming an iron thin film include inorganic iron acids such as iron sulfate, iron nitrate, iron phosphate, iron chloride, and iron bromide, and organic iron acids such as iron acetate, iron oxalate, iron citrate, and iron lactate. These can be used alone or as a mixture. The organic solvent contained in Coating Solution B is not particularly limited, and may be the same as the organic solvent that may be used in Coating Solution A. Coating Solution B may also contain a stabilizer that may be blended in Coating Solution A.
[0046] The coating and drying of the above-mentioned coating liquid A and coating liquid B can be carried out by using a known method.
[0047] (Surface modification treatment) The fibrous carbon nanostructure of the present invention is easily surface-modified when subjected to a surface-modifying treatment such as an oxidation treatment. Here, the surface modification treatment of the fibrous carbon nanostructure of the present invention is not particularly limited, and can be carried out using a surface modification treatment agent such as nitric acid, sulfuric acid, a mixed acid of nitric acid and sulfuric acid, ozone, fluorine gas, or hydrogen peroxide. Among them, from the viewpoint of obtaining a surface-modified fibrous carbon nanostructure with excellent dispersibility, the surface modification treatment of the fibrous carbon nanostructure of the present invention is preferably carried out using nitric acid, sulfuric acid, or a mixed acid of nitric acid and sulfuric acid, and more preferably a mixed acid of nitric acid and sulfuric acid. Moreover, the surface modification treatment conditions can be set according to the type of surface modification treatment agent used and the desired properties of the surface-modified fibrous carbon nanostructure.
[0048] The surface-modified fibrous carbon nanostructure obtained by subjecting the fibrous carbon nanostructure of the present invention to surface modification treatment can be well dispersed in a dispersion medium such as water, without particular limitation, without the use of a dispersant. The obtained fibrous carbon nanostructure dispersion can be used to manufacture various molded products (e.g., antistatic films, transparent conductive films, etc.).
[0049] When the properties of the fibrous carbon nanostructure to be surface-modified are unknown (i.e., when it is unclear whether it corresponds to the fibrous carbon nanostructure of the present invention), it is preferable to evaluate the fibrous carbon nanostructure using the evaluation method of the fibrous carbon nanostructure of the present invention described below, and to produce a surface-modified fibrous carbon nanostructure by subjecting the fibrous carbon nanostructure judged to be a good product to a surface-modified fibrous carbon nanostructure. By subjecting the fibrous carbon nanostructure judged to be a good product to a surface-modified fibrous carbon nanostructure, it is possible to obtain a surface-modified fibrous carbon nanostructure that has been satisfactorily surface-modified.
[0050] (Method for evaluating fibrous carbon nanostructures) The method for evaluating fibrous carbon nanostructures of the present invention includes the steps of: (A) performing thermogravimetric analysis of fibrous carbon nanostructures in a dry air atmosphere to obtain a first derivative of the thermogravimetric curve; (B) determining a symmetry coefficient of the peak of the first derivative of the thermogravimetric curve obtained in (A); and judging products having a symmetry coefficient of 3.70 or less obtained in (B) as non-defective products, and judging products having a symmetry coefficient of more than 3.70 as defective products. Thus, by judging products having a symmetry coefficient of 3.70 or less as non-defective products, fibrous carbon nanostructures that are susceptible to surface modification can be appropriately evaluated and selected. Note that the symmetry coefficient of the peak serving as the criterion for determining good and defective products is preferably 3.30 or less, more preferably 2.60 or less, still more preferably 2.00 or less, preferably 0.50 or more, more preferably 0.70 or more, and still more preferably 0.80 or more. If the symmetry coefficient of the peak of the first derivative curve is within the above range, it becomes easier to further surface-modify when performing a surface modification treatment such as an oxidation treatment. The thermogravimetric curve may be a thermogravimetric curve with the vertical axis being mass and the horizontal axis being temperature, or a thermogravimetric curve with the vertical axis being mass and the horizontal axis being time. Further, the first derivative curve of the thermogravimetric curve may be a temperature derivative curve with the vertical axis being differential thermogravimetry (DTG) and the horizontal axis being temperature, or a time derivative curve with the vertical axis being differential thermogravimetry (DTG) and the horizontal axis being time.
Example
[0051] Hereinafter, the present invention will be specifically described based on examples, but the present invention is not limited to these examples. In the following, “%” representing an amount is based on mass unless otherwise specified.
[0052] In the examples and comparative examples, the G / D ratio, average diameter, t-plot, total specific surface area, internal specific surface area, carbon purity, symmetry coefficient of the peak of the first derivative curve of the thermogravimetric curve, and surface modification processability of the fibrous carbon nanostructure containing CNT were measured or evaluated using the following methods, respectively.
[0053] <G / D ratio> Using a microscopic laser Raman system (manufactured by Thermo Fisher Scientific K.K., Nicolet Almega XR), measurement was performed on the fibrous carbon nanostructure near the center of the substrate. <Average diameter> The diameters (outer diameters) of 20 randomly selected fibrous carbon nanostructures obtained from an image obtained using a transmission electron microscope were measured and determined as the number average value. <t-plot, total specific surface area, and internal specific surface area> The measurement was performed using a BET specific surface area measuring device (BELSORP (registered trademark)-mini, manufactured by BEL Japan Co., Ltd.). <Carbon purity> Using a thermogravimetric analyzer (TG), the carbon purity (= (mass lost by combustion before reaching 800°C / initial mass) × 100 (%)) was calculated from the mass loss when the fibrous carbon nanostructure was heated to 800°C in air. <Symmetry coefficient> Using a thermogravimetric, differential and simultaneous thermal analyzer (manufactured by Bruker AXS, product name "TG-DTA2020SA"), the thermogravimetric curve of the fibrous carbon nanostructure was measured under conditions of a heating rate of 5°C / min and a dry air flow rate of 200 mL / min, and a first differential curve was obtained. [Temperature derivative curve] Here, in the case where the vertical axis of the thermogravimetric curve is mass and the horizontal axis is temperature, and the first derivative curve is, for example, a temperature derivative curve with the vertical axis being differential thermogravimetry (DTG) and the horizontal axis being temperature, as shown in FIG. 1(a), the symmetry coefficient W of the DTG peak of the fibrous carbon nanostructure can be calculated from the peak of the temperature derivative curve by the following formula (1): a / W b asked for. W a / W b =(T max -T a ) / (T b -T max ) ···(1) T max : Peak top temperature DTG max :Temperature T max Differential thermogravimetry in T a : Differential thermogravimetry value is DTG max Temperature at which the temperature becomes 1 / 10 of the normal value (low temperature side) T b : Differential thermogravimetry value is DTG max The temperature at which the temperature becomes 1 / 10 of the b >T a ) [For time derivative curve] In addition, when the vertical axis of the thermogravimetric curve is mass and the horizontal axis is time, and the first derivative curve is, for example, a time derivative curve with the vertical axis being differential thermogravimetry (DTG) and the horizontal axis being time, as shown in FIG. 1(b), the symmetry factor W of the DTG peak of the fibrous carbon nanostructure can be calculated from the peak of the time derivative curve by the following formula (2): a / W b asked for. W a / W b =(t max -t a ) / (t b -t max ) ···(2) t max : Peak top time DTG max : Time t max Differential thermogravimetry in t a : Differential thermogravimetry value is DTG max Time to 1 / 10 of (short time side) t b : Differential thermogravimetry value is DTG max The time it takes for the time to become 1 / 10 of the time (longer time side, t b >t a ) <Surface modification processability> 0.80 g of the obtained fibrous carbon nanostructure, 54.8 g of ion-exchanged water, and 83 mL of a mixed acid solution containing sulfuric acid (manufactured by Wako Pure Chemical Industries, Ltd., concentration 96-98%) and nitric acid (manufactured by Wako Pure Chemical Industries, Ltd., concentration 69-70%) in a volume ratio of 1:3 were added to a 300 mL flask equipped with a cooling tube and a stirring blade, and the mixture was then heated with stirring at an internal temperature of 110°C for 8 hours. 3.0 g of the resulting fibrous carbon nanostructure / mixed acid solution after the mixed acid treatment was weighed into a 50 mL sample bottle and diluted with 27.0 g of ion-exchanged water. After removing the supernatant, ion-exchanged water was added to make the liquid volume 30 mL. After adding 0.1% ammonia water to adjust the pH to 7.0, ultrasonic irradiation was performed at a frequency of 42 Hz for 50 minutes using an ultrasonic irradiation device (manufactured by Branson, product name "BRANSON5510") to obtain a dispersion of fibrous carbon nanostructures. [Evaluation of dispersion liquid] The obtained dispersion was centrifuged for 40 minutes at 20,000G using a centrifuge (manufactured by Beckman Coulter, product name "OPTIMA XL100K") and the supernatant was collected. This cycle was repeated three times to obtain 20 mL of a dispersion of fibrous carbon nanostructures after centrifugation. The obtained dispersion was visually inspected for the presence or absence of aggregates. In addition, a spectrophotometer (manufactured by JASCO, product name "V670") was used to measure the absorbance Ab1 (light path length 1 cm, wavelength 550 nm) of the dispersion before processing with a centrifuge, and the absorbance Ab2 (light path length 1 cm, wavelength 550 nm) of the dispersion after processing with a centrifuge. The dispersibility of the fibrous carbon nanostructures was evaluated by calculating the rate of decrease in absorbance due to centrifugation processing using the following formula. A smaller rate of decrease in absorbance indicates that the fibrous carbon nanostructures have been surface-modified more effectively and have better dispersibility. Absorbance reduction rate (%)={1-(Ab2 / Ab1)}×100 [Evaluation of molded products (films)] The obtained dispersion was applied to a glass substrate using a bar coater #2 and then dried at 130° C. for 10 minutes to form a film made of fibrous carbon nanostructures on the glass substrate. The obtained film was observed under an optical microscope (magnification 100x) to confirm the presence or absence of agglomerates (diameter 30 μm or more) of the fibrous carbon nanostructures visible in the field of view of the microscope, thereby evaluating the dispersibility of the fibrous carbon nanostructures. The fewer the number of agglomerates of the fibrous carbon nanostructures, the better the surface modification of the fibrous carbon nanostructures is, indicating that the dispersibility of the fibrous carbon nanostructures is excellent.
[0054] Example 1 <Production of catalyst substrate> 0.19 kg of aluminum tri-sec-butoxide was dissolved in 10 L (7.8 kg) of 2-propanol. 0.09 kg of triisopropanolamine was added and dissolved as a stabilizer to prepare coating solution A. 174 mg of iron acetate was dissolved in 10 L (7.8 kg) of 2-propanol. 0.019 kg of triisopropanolamine was added and dissolved as a stabilizer to prepare coating solution B. The above-mentioned coating solution A was applied to the surface of a SUS430 substrate made of an Fe-Cr alloy as a flat substrate to form an alumina thin film (catalyst support layer) with a thickness of 40 nm. Next, the above-mentioned coating solution B was applied to the alumina thin film provided on the substrate to obtain a catalyst substrate having an iron thin film with a thickness of 3 nm. <Synthesis of fibrous carbon nanostructures> The above-mentioned catalyst substrate was subjected to the formation process (reduction process), synthesis process, and cooling process in succession to synthesize an oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs). In the synthesis process, the catalyst substrate was fed with a raw material gas (composition (by volume): ethylene: 20%, H 2 O: 55-440 ppm, N: 2 : the remainder) was supplied at a flow rate of 150 sLm. The obtained fibrous carbon nanostructure containing CNTs had a G / D ratio of 3.7, an average diameter of 4 nm, and a carbon purity of 99.9%. Measurements using a Raman spectrometer showed that the 100–300 cm -1 A radial breathing mode (RBM) peak was observed in the low wavenumber region of 100 nm. The t-plot of the fibrous carbon nanostructure obtained from the adsorption isotherm was bent upward in a convex shape. The bending point was at t = 0.7 nm, and the total specific surface area S1 was 1270 m 2 / g, and the internal specific surface area S2 is 290 m 2 / g and S2 / S1 was 0.23. The symmetry coefficient of the peak in the first derivative curve of the thermogravimetry curve and the surface modification processability of the obtained fibrous carbon nanostructure were evaluated. The results are shown in Table 1. The symmetry coefficient of the peak was determined from the temperature derivative curve of the thermogravimetry curve.
[0055] Example 2 An oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs) was synthesized in the same manner as in Example 1, except that the concentration of ethylene in the synthesis step was set to 17%. The obtained fibrous carbon nanostructure containing CNTs had a G / D ratio of 2.9, an average diameter of 4 nm, and a carbon purity of 99.9%. Measurements using a Raman spectrometer showed that the 100–300 cm -1 A radial breathing mode (RBM) peak was observed in the low wavenumber region of 1000 nm. The t-plot of the fibrous carbon nanostructure obtained from the adsorption isotherm was bent upward in a convex shape. The bending point was at t = 0.7 nm, and the total specific surface area S1 was 1130 m 2 / g, and the internal specific surface area S2 is 240 m 2 / g and S2 / S1 was 0.21. The symmetry coefficient of the peak in the first derivative curve of the thermogravimetry curve and the surface modification processability of the obtained fibrous carbon nanostructure were evaluated. The results are shown in Table 1. The symmetry coefficient of the peak was determined from the temperature derivative curve of the thermogravimetry curve.
[0056] Example 3 An oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs) was synthesized in the same manner as in Example 1, except that the concentration of ethylene in the synthesis step was 14%. The obtained fibrous carbon nanostructure containing CNTs had a G / D ratio of 2.8, an average diameter of 4 nm, and a carbon purity of 99.9%. Measurements using a Raman spectrometer showed that the 100–300 cm -1 A radial breathing mode (RBM) peak was observed in the low wavenumber region of 1000 nm. The t-plot of the fibrous carbon nanostructure obtained from the adsorption isotherm was bent upward in a convex shape. The bending point was at t = 0.7 nm, and the total specific surface area S1 was 1240 m 2 / g, and the internal specific surface area S2 is 230 m 2 / g and S2 / S1 was 0.19. The symmetry coefficient of the peak in the first derivative curve of the thermogravimetry curve and the surface modification processability of the obtained fibrous carbon nanostructure were evaluated. The results are shown in Table 1. The symmetry coefficient of the peak was determined from the temperature derivative curve of the thermogravimetry curve.
[0057] Comparative Example 1 An oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs) was synthesized in the same manner as in Example 1, except that the concentration of ethylene in the synthesis step was 10%. The obtained fibrous carbon nanostructure containing CNTs had a G / D ratio of 3.4, an average diameter of 4 nm, and a carbon purity of 99.9%. Measurements using a Raman spectrometer showed that the 100–300 cm -1 A radial breathing mode (RBM) peak was observed in the low wavenumber region of 1000 nm. The t-plot of the fibrous carbon nanostructure obtained from the adsorption isotherm was bent upward in a convex shape. The bending point was at t = 0.7 nm, and the total specific surface area S1 was 1320 m 2 / g, and the internal specific surface area S2 is 55m 2 / g and S2 / S1 was 0.04. The symmetry coefficient of the peak in the first derivative curve of the thermogravimetry curve and the surface modification processability of the obtained fibrous carbon nanostructure were evaluated. The results are shown in Table 1. The symmetry coefficient of the peak was determined from the temperature derivative curve of the thermogravimetry curve.
[0058] [Table 1]
[0059] It is clear from Table 1 that the fibrous carbon nanostructures of Examples 1 to 3 are better surface-modified and have better dispersibility than the fibrous carbon nanostructure of Comparative Example 1. [Industrial Applicability]
[0060] According to the present invention, it is possible to provide a fibrous carbon nanostructure which is easy to subject to a surface modification treatment. Furthermore, according to the present invention, it is possible to provide a surface-modified fibrous carbon nanostructure which has been subjected to a satisfactory surface modification treatment.
Claims
1. Contains carbon nanotubes, the symmetry coefficient of the peak of the first differential curve of the thermogravimetric curve obtained by thermogravimetric analysis in a dry air atmosphere is 3.70 or less; A fibrous carbon nanostructure having a ratio of G band peak intensity to D band peak intensity in a Raman spectrum of 0.5 or more and 5.0 or less.
2. The fibrous carbon nanostructure according to claim 1 , wherein the first derivative curve is a temperature derivative curve or a time derivative curve of the thermogravimetric curve.
3. 3. The fibrous carbon nanostructure according to claim 1, wherein a t-plot obtained from an adsorption isotherm exhibits an upwardly convex shape.
4. The fibrous carbon nanostructure according to claim 3, wherein the inflection point of the t-plot is in the range of 0.2≦t(nm)≦1.
5.
5. 5. The fibrous carbon nanostructure according to claim 1, wherein the total specific surface area S1 and the internal specific surface area S2 obtained from a t-plot obtained from the adsorption isotherm satisfy the relationship: 0.05≦S2 / S1≦0.
30.
6. The fibrous carbon nanostructure according to any one of claims 1 to 5, wherein the carbon nanotubes are single-walled carbon nanotubes.
Citation Information
Patent Citations
Method for growing high-quality semiconductor single-walled carbon nanotube through in-situ weak hydrogen etching
CN103011130A
The effect of hydrocarbon and transport gas materials on the efficiency and quality of grown single-walled nanotubes.
JP2011519809A
Highly soluble carbon nanotubes with improved conductivity
JP2014527010A
Coating method of solid powder and manufacturing method for carbon nanotube using the same
KR101210577B1
Carbon-based nanostructure membranes
US20170263946A1
Cited By
Image processing apparatus, method for controlling image processing apparatus, storage medium, and computer program product
CN122554724A